Disaster risk management in business education setting the tone (2016)
Looking for windows of opportunity to mainstream disaster risk management within business education, in 2015, the United Nations Office for Disaster Reduction’s (UNISDR) Private Alliance for Disaster Resilient Societies (arise), partnered with Florida International University’s Extreme Events Institute (FIU-EEI) and 12 international leading business schools. This partnership began with a call for White Papers to propose innovative approaches to integrate cutting edge disaster management content into business education programs and other academic offerings, based on seven themes or niches identified: (1) Strategic Investment and Financial Decisions; (2) Generating Business Value; (3) Sustainable Management; (4) Business Ethics and Social Responsibility; (5) Business Continuity Planning; (6) Disaster Risk Metrics; and (7) Risk Transfer. In March 2016, an international workshop was held in Toronto, Canada to present the White Papers prepared by the business schools, and discuss the most appropriate approaches for addressing the areas of: teaching and curriculum; professional development and extension programs; internships and placement; research opportunities; and partnerships and collaboration. Finally, the group proposed goals for advancing the implementation phase of the business education initiatives, and to propose mechanisms for monitoring and follow-up